Use of the Natural Circulation Flow Map for Natural Circulation Systems Evaluation - M. Cherubini; W. Giannotti; D. Araneo; F. D'Auria (Science and Technology of Nuclear Installations)
The aim of this paper is to collect and resume the work done to build and develop, at the University of Pisa, an engineering tool related to the natural circulation. After a brief description of the different loop flow regimes in single phase and two phase, the derivation of a suitable tool to judge the NC performance in a generic system is presented. Finally, an extensive comparison among the NC performance of various nuclear power plants having different design is done to show a practical application of the NC flow map.